Pengaruh Dakwah Melalui Media Digital Canva dalam Meningkatkan Pemahaman Agama di Kalangan Mahasiswa - Hairani, Atikah; Sulastri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This research aims 1) to analyze whether da'wah through digital media in the form of Canva has an effect in increasing understanding of religion among students, 2) to analyze whether da'wah through digital media in the form of Canva has a positive or negative effect in increasing understanding of religion among students. This research uses the method quantitative involving 77 students from 3 study programs at the Islamic University of North Sumatra Pematangsiantar. The research data was obtained through distributing an online questionnaire via Google Form to look at trends in data access activities via Canva digital media among students and to determine the increase in understanding of religion among students. Then the data was processed using the SPSS.16 application using simple regression analysis and the results of the analysis using simple regression Anava test obtained a significant value of 0.000<0.05, thus the Canva digital preaching media had an influence in increasing understanding of religion among students, then it was obtained The coefficient value is 0.820, this shows that the influence is positive. The magnitude of the influence is 84.9%.